Simultaneous determination of multiple components in rat plasma by UPLC-MS/MS for pharmacokinetic studies after oral administration of Pogostemon cablin extract - Zhu, Yameng; Ouyang, Huizi; Lv, Zhenguo; Yao, Guangzhe; Ge, Minglei; Cao, Xiunan; Chang, Yanxu; He, Jun (Frontiers in Pharmacology, 2024)
Introduction:Pogostemon cablin (PC) is used in traditional Chinese medicine and food, as it exerts pharmacological effects, such as immune-modulatory, antibacterial, antioxidant, antitumor, and antiviral. Currently, the pharmacokinetics (PK) studies of PC mainly focus on individual components. However, research on these individual components cannot reflect the actual PK characteristics of PC after administration. Therefore, the simultaneous determination of multiple components in rat plasma using UPLC-MS/MS was used for the pharmacokinetic study after oral administration of PC extract in this study, providing reference value for the clinical application of PC. Methods: In the present study, a reliable and sensitive ultra-high performance liquid chromatography/tandem mass spectrometry (UPLC-MS/MS) method was developed and validated for the simultaneous determination of 15 prototype components (vanillic acid, vitexin, verbascoside, isoacteoside, hyperoside, cosmosiin, apigenin, β-rhamnocitrin, acacetin, ombuin, pogostone, pachypodol, vicenin-2, retusin, and diosmetin-7-O-β-D-glucopyranoside) in rat plasma after oral administration of the PC extract. Plasma samples were prepared via protein precipitation using acetonitrile, and icariin was used as the internal standard (IS). Results: The intra-day and inter-day accuracies ranged from −12.0 to 14.3%, and the precision of the analytes was less than 11.3%. The extraction recovery rate of the analytes ranged from 70.6−104.5%, and the matrix effects ranged from 67.4−104.8%. Stability studies proved that the analytes were stable under the tested conditions, with a relative standard deviation lower than 14.1%. Conclusion: The developed method can be applied to evaluate the PK of 15 prototype components in PC extracts of rats after oral administration using UPLC-MS/MS, providing valuable information for the development and clinical safe, effective, and rational use of PC.